2015
DOI: 10.17305/bjbms.2015.432
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 and Vitamin D levels may be associated with systolic and diastolic blood pressure values and hearth rate in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common causes of female infertility. It affects nearly 5-10% of young women. It is characterized by the presence of hirsutism, acne, anovulation, hyperandrogenism, polycystic ovaries, and infertility [1]. Many mechanisms have been reported to be responsible for the pathophysiology of PCOS. The condition is thought to be determined by complex interactions between the hypothalamic-pituitary-ovarian or hypothalamic-pituitary-adrenal axis functions and metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
3
23
3
1
Order By: Relevance
“…Their results were similar to those reported by Tan et al (28) who compared the levels of Nesfatin-1 in 38 adult subjects. Sahin et al (29) found higher levels of Nesfatin-1 in polycystic ovary syndrome than healthy controls and also reported that these values positively correlated with SBP and DBP. In our study, the Nesfatin-1 levels in both groups were between the commercial kit normal values.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their results were similar to those reported by Tan et al (28) who compared the levels of Nesfatin-1 in 38 adult subjects. Sahin et al (29) found higher levels of Nesfatin-1 in polycystic ovary syndrome than healthy controls and also reported that these values positively correlated with SBP and DBP. In our study, the Nesfatin-1 levels in both groups were between the commercial kit normal values.…”
Section: Discussionmentioning
confidence: 92%
“…In our study Nesfatin-1 was independently associated with hypertension and was predictive of hypertension in obese subjects. Zhao et al (23) and Sahin et al (29) found a positive correlation between Nesfatin-1 level and BP. However we did not find significant correlation between Nesfatin-1 and BP.…”
Section: Discussionmentioning
confidence: 96%
“…Dai et al showed that lower nesfatin-1 concentration may have an important role in the development of acute myocardial infarction (17). Sahin et al reported that Nesfatin-1 levels play an important role in the pathogenesis of hypertension in patients with polycystic ovary syndrome (18). Angelone et al demonstrated that Nesfatin-1 elicits an incisive influence on the heart by depressing contractility and relaxation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that there is an association between serum nesfatin-1 concentrations and development and severity of peripheral arterial disease (16), acute myocardial infarction (17), and hypertension (18). However, it was not studied yet the effects of functional gene variations of NUCB2/Nesfatin-1 gene on CAD risk.…”
Section: Introductionmentioning
confidence: 99%
“…Wysoki poziom krążącej nesfatyny-1 jest związany ze wzrostem skurczowego i rozkurczowego ciśnienia krwi oraz rytmu serca (ryc. 1) (80). Biorąc pod uwagę fakt, iż tkanka tłuszczowa jest źródłem nesfatyny-1, a wielkość sekrecji jest związana z dietą (78), nesfatyna-1 może odgrywać istotną rolę w oddziaływaniu otyłości na rozwój chorób układu sercowo-naczyniowego (25).…”
Section: Nesfatyna-1 a Otyłośćunclassified